Regional homogeneity and functional connectivity in resting-state brain activity in tinnitus patients - Haidi Yang; Haiyan Lin; Xiaofeng Lin; Xueyuan Zhang; Hao Xiong; Yiqing Zheng (Journal of Bio-X Research, 2020)
Abstract. Objective:. Subjective tinnitus is characterized by the perception of sound in the absence of any external auditory stimuli. This perceived sound may be related to altered intrinsic neural activity generated along the central auditory pathway. This retrospective study was designed to investigate regional homogeneity and functional connectivity in the resting-state brain activity of patients with tinnitus. Methods:. We recruited tinnitus patients with normal hearing or mild hearing loss (n = 17) and age-matched healthy controls (n = 20), and examined regional homogeneity and functional connectivity in resting-state brain activity using resting-state functional magnetic resonance imaging data. The present study protocol was approved by the Institutional Review Board on Experimental Ethics at Sun Yat-sen University, China (approval No. SYSEC-KY-KS-2019-083). Results:. Compared with normal controls, patients with tinnitus had significantly decreased regional homogeneity in the anterior lobe of the cerebellum and increased homogeneity in the inferior frontal gyrus (P < 0.05 corrected at a cluster-level). In addition, tinnitus patients showed enhanced functional connectivity between the inferior frontal gyrus and the ventral striatum and midbrain, as well as increased connectivity between the cerebellum and ventromedial prefrontal cortex (P < 0.05 corrected at a cluster-level). We also found decreased connectivity between the cerebellum and the anterior insula compared with controls (P < 0.05 corrected at a cluster-level). Conclusion:. Abnormal connectivity in non-auditory brain structures, particularly those related to emotion processing, may be associated with tinnitus persistence.